Defying Death and the Natural Order: True Terror in Alfred Hitchcock's The Birds. Issue 3 (23rd March 2023) - Brackens, Andrew
This article explores the shame that derives from human mortality and how it is put on display in Alfred Hitchcock's film The Birds . Using the concepts of the natural order and the animalistic other, this article analyzes the film's commentary on humanity's inability to accept death willingly, going out of their way to repress it and disrespect it. Unfortunately for the characters in the film, the birds embody a force of nature that remind the humans with their animalistic gaze that they are not above the laws of nature, sharing the same fate as every living being.